The Effect of Corrective Feedback on Performance in Basic Cognitive Tasks: An Analysis of RT Components. Issue 4 (20th December 2016) - Moret-Tatay, Carmen; Leth-Steensen, Craig; Irigaray, Tatiana Quarti; Argimon, Irani I. L.; Gamermann, Daniel; Abad-Tortosa, Diana; Oliveira, Camila; Sáiz-Mauleón, Begoña; Vázquez-Martínez, Andrea; Navarro-Pardo, Esperanza; Fernández de Córdoba Castellá, Pedro
The current work examines the effect of trial-by-trial feedback about correct and error responding on performance in two basic cognitive tasks: a classic Stroop task ( n = 40) and a color-word matching task ( n = 30). Standard measures of both RT and accuracy were examined in addition to measures obtained from fitting the ex-Gaussian distributional model to the correct RTs. For both tasks, RTs were faster in blocks of trials with feedback than in blocks without feedback, but this difference was not significant. On the other hand, with respect to the distributional analyses, providing feedback served to significantly reduce the size of the tails of the RT distributions. Such results suggest that, for conditions in which accuracy is fairly high, the effect of corrective feedback might either be to reduce the tendency to double-check before responding or to decrease the amount of attentional lapsing.